A Revolução cidadã : o governo Rafael Correa e os movimentos indígenas no Equador - Menon, Gustavo (2013)
The objective of this work is to contribute to the analysis of articulation between social movements and the Correa government in Ecuador from 2007 to 2012. The largest share of the state in controlling the oil sector, the challenge of considerable public debt (internal and external), the criticism of the dollarization of the economy, foreign policy alignment with the Bolivarian bloc, the proclamation of a new constitution that institutionalizes new rights, including indigenous communities - here are some aspects of that government.. In any country, changes of this magnitude are not due to the characteristics of a demiurgic government, however important the performance of this. Here we want to emphasize that these advances was also determined by intense struggle, with many advances and retreats, times of expansion and contraction of social movements in Ecuador. In the mentioned period, the government and social movements, assumed, of different and often contradictory ways, anti-neoliberal positions, which led to a number of significant changes in the social formation. Far from predetermined, the ramifications of this process are open, because there is the active presence of conservative hegemony forces by neoliberalism. These make up a tab of the range of possibilities that goes through the new-developmentalism and extends to policies anti-systemic strong character